Cadherin and catenin biology represent a global mechanism for epithelial cancer progression. Issue 6 (December 1997) - Jankowski, J A; Bruton, R; Shepherd, N; Sanders, D S
Abstract : The cell undergoes a diverse range of stimulations including growth factor activation and signal transduction from adhesion receptors, such as cadherins. In the absence of a mitogenic signal from outside the cell, beta catenin is sequestered in complexes with the product of the adenomatous polyposis coli (APC) gene and a serine threonine glycogen kinase (GSK 3 beta) enabling degradation of free beta catenin. Residual catenins hold cells together by binding to cadherins both at adherens junctions and the actin cytoskeleton. When a mitotic signal is delivered by the wnt pathway, GSK 3 beta is antagonised so that beta catenin can no longer be degraded. Cytosolic concentrations rise and binding to other newly synthesised proteins occurs, especially transcription factors that are transported to the nucleus, such as lymphocyte enhancing factor and T cell factor. This article discusses the signalling between mitogenic and adhesion pathways and suggests that it is a global mechanism for development, differentiation, and disease. These changes in catenin and APC biology may not be sufficient alone to transform cells fully but they appear to be a necessary final common pathway for several cancers of the mucous secreting crypts (including Barrett's oesophageal lesions and colorectal cancer) or stratified secreting epithelium (melanoma) before invasion.